Metal-organic framework membranes with single-atomic centers for photocatalytic CO2 and O2 reduction - Hao, Yu-Chen; Chen, Li-Wei; Li, Jiani; Guo, Yu; Su, Xin; Shu, Miao; Zhang, Qinghua; Gao, Wen-Yan; Li, Siwu; Yu, Zi-Long; Gu, Lin; Feng, Xiao; et al. (Nature communications, 2021)
The demand for sustainable energy has motivated the development of artificial photosynthesis. Yet the catalyst and reaction interface designs for directly fixing permanent gases (e.g. CO 2 , O 2 , N 2 ) into liquid fuels are still challenged by slow mass transfer and sluggish catalytic kinetics at the gas-liquid-solid boundary. Here, we report that gas-permeable metal-organic framework (MOF) membranes can modify the electronic structures and catalytic properties of metal single-atoms (SAs) to promote the diffusion, activation, and reduction of gas molecules (e.g. CO 2, O 2 ) and produce liquid fuels under visible light and mild conditions. With Ir SAs as active centers, the defect-engineered MOF (e.g. activated NH 2 -UiO-66) particles can reduce CO 2 to HCOOH with an apparent quantum efficiency (AQE) of 2.51% at 420 nm on the gas-liquid-solid reaction interface. With promoted gas diffusion at the porous gas-solid interfaces, the gas-permeable SA/MOF membranes can directly convert humid CO 2 gas into HCOOH with a near-unity selectivity and a significantly increased AQE of 15.76% at 420 nm. A similar strategy can be applied to the photocatalytic O 2 -to-H 2 O 2 conversions, suggesting the wide applicability of our catalyst and reaction interface designs. Photoreduction of permanent gas faces challenges in reactant diffusion and activation at the three-phase interface. Here the authors showed porous metal-organic framework membranes decorated by metal single atoms can boost the photoreduction of CO 2 and O 2 at the high-throughput gas-solid interface.